Abiotic Reduction of Mercury(II) in the Presence of Sulfidic Mineral Suspensions - Coulibaly, Mariame; Mazrui, Nashaat M.; Jonsson, Sofi; Mason, Robert P. (Frontiers in Environmental Chemistry, 2021)
Monomethylmercury (CH3Hg) is a neurotoxic pollutant that biomagnifies in aquatic food webs. In sediments, the production of CH3Hg depends on the bacterial activity of mercury (Hg) methylating bacteria and the amount of bioavailable inorganic divalent mercury (HgII). Biotic and abiotic reduction of HgII to elemental mercury (Hg0) may limit the pool of HgII available for methylation in sediments, and thus the amount of CH3Hg produced. Knowledge about the transformation of HgII is therefore primordial to the understanding of the production of toxic and bioaccumulative CH3Hg. Here, we examined the reduction of HgII by sulfidic minerals (FeS(s) and CdS(s)) in the presence of dissolved iron and dissolved organic matter (DOM) using low, environmentally relevant concentrations of Hg and ratio of HgII:FeS(s). Our results show that the reduction of HgII by Mackinawite (FeS(s)) was lower (<15 % of the HgII was reduced after 24 h) than when HgII was reacted with DOM or dissolved iron. We did not observe any formation of Hg0 when HgII was reacted with CdS(s) (experiments done under both acidic and basic conditions for up to four days). While reactions in solution were favorable under the experimental conditions, Hg was rapidly removed from solution by co-precipitation. Thermodynamic calculations suggest that in the presence of FeS(s), reduction of the precipitated HgII is surface catalyzed and likely involves S-II as the electron donor. The lack of reaction with CdS may be due to its stronger M-S bond relative to FeS, and the lower concentrations of sulfide in solution. We conclude that the reaction of Hg with FeS(s) proceeds via a different mechanism from that of Hg with DOM or dissolved iron, and that it is not a major environmental pathway for the formation of Hg0 in anoxic environments.